A Fatal Case of Primary Amoebic Meningoencephalitis from Recreational Waters - Edward Hamaty; Saif Faiek; Minesh Nandi; David Stidd; Manish Trivedi; Hari Kandukuri (Case Reports in Critical Care)
Background. Naegleria Fowleri is a single-cell, thermophilic amphizoid amoeba, and a rare known causative agent for primary amoebic meningoencephalitis with >97% mortality rate. The amoeba resides in freshwater lakes and ponds but can also survive in inadequately chlorinated pools and recreational waters. The mode of infection includes activities such as diving or jumping into freshwater or submerging the head under the water. Although most commonly seen in the southern United States, it is essential to keep this clinical suspicion in mind regardless of geography, as presenting symptoms can be very similar to classic bacterial meningitis. Case Summary. We report the first-ever case in the state of New Jersey of a 29-year-old male presented after a visit to a recreational water park in Texas five days before his presentation with altered mental status. In ICU, his ICP remained refractory to multiple therapies, including antibiotics and antivirals, external ventriculostomy drain, hypertonic saline, pentobarbital-induced coma, and bilateral hemicraniectomies. The CSF analysis revealed trophozoites indicating a protozoan infection, which we diagnosed in the neurocritical unit, and the patient was then immediately started with treatment that included amphotericin B, rifampin, azithromycin, and fluconazole. This suspicion was promptly confirmed by the Center for Disease Control (CDC). Unfortunately, despite all the aggressive intervention by the multidisciplinary team, the patient did not survive. Conclusion. As per the CDC, only four people out of 143 known infected individuals in the United States from 1962 to 2017 have survived. Symptoms start with a median of 5 days after exposure to contaminated water. Given the rarity of this case and its very high mortality rate, it is crucial to diagnose primary amoebic meningoencephalitis accurately as its presentation can mimic bacterial meningitis. It is vital to obtain a careful and thorough history, as it can aid in prompt diagnosis and treatment.